2019
DOI: 10.31311/jeco.v3i2.6059
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pelatihan Terhadap Prestasi Kerja Karyawan Pada Unit HCBP Pt Telekomunikasi Indonesia (Tbk)

Abstract: Tujuan dari penelitian ini untuk mengetahui pengaruh dan menganalisis bagaimana pelatihan yang diberikan oleh perusahaan, bagaimana prestasi kerja yang dihasilkan oleh para karyawan, dan besarnya pengaruh pelatihan terhadap prestasi kerja karyawan pada Unit HCBP (Human Capital Business Partner) PT Telekomunikasi Indonesia (Tbk). Metode penelitian yang digunakan adalah metode kuantitatif dengan jenis penelitian deskriptif  kausalitas. Pengambilan sampel yang dilakukan menggunakan teknik sampling jenuh, dengan j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
1
3
0
8
Order By: Relevance
“…The results of statistical tests showed that there was a significant effect of training objectives on employee performance, seen from the p-value 0.046 <0.05 and the coefficient value 0.080. The results of this research are in line with (Nursyahputri & Saragih, 2019)that is, there is a positive and significant influence between the training objectives on employee performance. The purpose of the training is to increase the quality and work productivity of these employees.…”
Section: Training Objectives On Employee Performancesupporting
confidence: 84%
See 3 more Smart Citations
“…The results of statistical tests showed that there was a significant effect of training objectives on employee performance, seen from the p-value 0.046 <0.05 and the coefficient value 0.080. The results of this research are in line with (Nursyahputri & Saragih, 2019)that is, there is a positive and significant influence between the training objectives on employee performance. The purpose of the training is to increase the quality and work productivity of these employees.…”
Section: Training Objectives On Employee Performancesupporting
confidence: 84%
“…The instructor is a teacher who plays an important role in the success of the training program (Nursyahputri & Saragih, 2019). According to (Hasibuan, 2016)…”
Section: Training Instructormentioning
confidence: 99%
See 2 more Smart Citations
“…Pelatihan menjadi salah satu aktivitas yang umum di lakukan dalam organisasi sebab setiap organisasi berharap dengan adanya pelatihan yang tepat dapat meningkatkan kemampuan karyawan dalam menyelesaikan pekerjaannya dengan benar dan tepat (Nursyahputri & Saragih, 2019). Sedangkan, konsekuensi dari kurangnya pembekalan dan pelatihan yang tepat yaitu karyawan akan sulit beradaptasi dengan perubahan kondisi atau lingkungan kerja yang semakin krisis sehingga dapat mengakibatkan menurunnya semangat kerja karyawan (Fizia & Muttaqin, 2018).…”
unclassified